Marine pollution differentiation with stable isotopes of groundwater - Mance, Diana; Mance, Davor, ekonomist; Vukić Lušić, Darija (2018)
Stock and flow pollution differentiation is the basis for efficient pollution-abatement mechanism designs. The focus of our research has been marine pollution from land-based sources. Stable isotope analysis of groundwater is an acknowledged method for karst aquifer characterisation. We have tested whether stable isotopes of water, when used as a proxy for groundwater dynamics in the karst, could also be used as an indicator of marine pollution differentiation in terms of flow and stock pollution. The focus has been on two close coastal locations characterized by differences in terms of open and closed sea as well as anthropogenic pressure. A static Estimated General Least Squares (EGLS) statistical model described the closed bay location suggesting stock pollution. For a good description of the open sea location, we have had to resort to dynamic Generalised Method of Moments (GMM) statistical modelling, indicating flow pollution. Stable isotopes of groundwater together with appropriate statistical tools have proved to be a useful tool of marine pollution differentiation into stock or flow.
Bibliografija: 25 jed.
Abstract.
Keywords: Onečišćenje mora -- Mikrobi -- Izotopi kisika -- Podzemne vode